Analysing Resource Use Efficiency and Determinants of Catfish Output in Ondo State, Nigeria - Oladoyin, Olanrewaju; Bello, Temitope Olanrewaju; Ijigbade, Justin Orimisan; Adaba, Oluwajuwon Emmanuel; Ilesanmi, Julius Olumide (PT. Riset Press International, 2025)
This study evaluated resource use efficiency in catfish production in Ondo East Local Government Area, Ondo State, Nigeria. A multistage sampling technique was employed to select 150 catfish farmers across five purposively chosen communities. Structured questionnaires were used to collect primary data, which were analysed using descriptive statistics, budgetary analysis, and multiple regression models. Findings indicate that the average age of respondents was 45 years, with most being male (80%), married (80%), and formally educated (97.3%). The mean household size was five, and the average farming experience was 11 years. The majority (87.3%) sourced fingerlings through purchase, and over half (51.3%) relied on personal savings as their main capital source. The mean farm size was 6.17 units. Profitability analysis revealed that for every ₦1.00 invested, farmers earned ₦3.90, confirming the viability of catfish farming in the area. Regression analysis identified fingerlings, feed, labour, and pesticides as significant inputs influencing output (p < 0.05), while farm size and fertiliser had no significant effect. Efficiency analysis showed underutilization of fingerlings (12.6) and pesticides (1.2), while inputs such as feed, labour, fertiliser, and farm size were overutilized. Major production constraints included limited access to credit (98.7%), high feed costs (97.3%), and pollution (83.3%). The study concludes that while catfish farming is profitable, inefficiencies and structural challenges persist. It recommends improving farmers’ access to credit, promoting investment in fingerlings, and encouraging youth participation to enhance productivity and reduce rural unemployment.